IMPLEMENTATION OF THE ACADEMIC SUPERVISION OF THE SCHOOL PRINCIPAL IN IMPROVING TEACHERS PERFORMANCE ON TEACHING AND LEARNING PROCESS - Wahyuni, Sri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is a school action research conducted in 2 cycles. This study aims to determine the performance of teachers with the implementation of academic supervision of school principals. This research was conducted at SMA N 10 Pekanbaru. The subjects of this study were 4 subject teachers whose performance was still not optimal. The results of the research proved in the recapitulation of supervision of the first cycle to get an average value of 89.2. Although the results of the study showed good results, to look for a comparison, the research was still carried out in the second cycle. After conducting research in the second cycle, the results of the supervision assessment increased to 91.5. For the assessment of the performance of teachers of SMA N 10 in cycles 1 and 2, an average of 89.5 was obtained. Based on the results of the study, it can be concluded that the implementation of supervision of the school principal can improve teachers performance in teaching and learning.